Sonochemical Synthesis of Gold Nanoparticles by Using High Intensity Focused Ultrasound - Yusof, N.S.M.; Ashokkumar, M. (Wiley-VCH Verlag Berlin, 2015)
The sonochemical synthesis of gold nanoparticles (GNPs) with different shapes and size distributions by using high‐intensity focused ultrasound (HIFU) operating at 463 kHz is reported. GNP formation proceeds through the reduction of Au3+ to Au0 by radicals generated by acoustic cavitation. TEM images reveal that GNPs show irregular shapes at 30 W, are primarily icosahedral at 50 W and form a significant amount of nanorods at 70 W. The size of GNPs decreases with increasing acoustic power with a narrower size distribution. Sonochemiluminescence images help in the understanding of the effect of HIFU in controlling the size and shapes of GNPs. The number of radicals that form and the mechanical forces that are generated control the shape and size of the GNPs. UV/Vis spectra and TEM images are used to propose a possible mechanism for the observed effects. The results presented demonstrate, for the first time, that the HIFU system can be used to synthesise size‐ and shape‐controlled metal nanoparticles.